2007
DOI: 10.1097/mlr.0b013e3180546879
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health Care Utilization for Respiratory Symptoms in the First Year of Life

Abstract: Child and parent characteristics, besides complaints per se, play an important role in health care utilization for respiratory illnesses in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
2
12
0
3
Order By: Relevance
“…Although in a previous article [21] we described that consultations are not only associated with severity of symptoms, the same results were found after adjustment for risk factors associated with consultations for respiratory illnesses. Although there is standardisation in primary care, as all general practitioners use ICPC, it is possible that different general practitioners classified wheezing illnesses in a different way.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although in a previous article [21] we described that consultations are not only associated with severity of symptoms, the same results were found after adjustment for risk factors associated with consultations for respiratory illnesses. Although there is standardisation in primary care, as all general practitioners use ICPC, it is possible that different general practitioners classified wheezing illnesses in a different way.…”
Section: Discussionsupporting
confidence: 68%
“…The models were adjusted for maternal smoke exposure during pregnancy, parental allergy and the presence of siblings, because these variables may be associated with lung function and wheezing illnesses. Because we have previously showed that daycare visits, ethnicity and maternal age .30 years are determinants of consultations for respiratory illnesses [21], we also adjusted the regression analyses with consultations or asthma as outcome for these potential confounders, additionally to the above-mentioned variables. The linear regression model was additionally adjusted for length and weight at the spirometry measurement.…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings are in line with reports of genetic infl uence on disease susceptibility, 8 health-seeking behavior, 7,25 and the attitude of the caregivers or parents regarding medication use. 26 In our study, we found that parental asthma was positively associated with prescribing asthma medications.…”
Section: Family Infl Uencesupporting
confidence: 77%
“…It is well recognised that RW in infants significantly affects the quality of life of patients and their families1 and represents an important cause for using healthcare resources, thus resulting in a large health economic impact 2 3. In a prevalence study in young children aged 1–5 years from the USA and Europe, it was found that one-third of them suffered from recurrent asthma-like symptoms 4.…”
Section: Introductionmentioning
confidence: 99%